Kekuasaan yang Bekerja Melalui Perlawanan: Kasus Penguasaan Hutan oleh Masyarakat dan Perusahaan - Maring Prudensius (Antropologi Indonesia, 2013)
This article analyze model of resistance between the local community and private company withinspired to perspective of power relation. Analysis based on the research about forest tenure by the local community and private company in Praha Village, Jambi. The research inspired qualitative approach with methods of indepth interview and participatory observation. The local community and private company constitute stakeholders that have interest on the forest resources. Complexity of the stakeholders’s interest were expressed through models of the social relation that were conflict, collaboration, and resistance. Dynamics of the social relation are reality of the power relation. Resistance are strategy of power relation with special features that each other stakeholders focus on the strategy to realize the each other goals and indirectly to fail the strategy of others.Key words: Power, resistance, strategy of power, forest tenure, local community, private company